The Determinants of Venture Capital: Additional Evidence - Bruno van Pottelsberghe de la Potterie; Astrid Romain (Deutsche Bundesbank, 2004)
This paper attempts to identify and evaluate the main determinants of venture capital (VC). We develop a theoretical model where macroeconomic conditions, technological opportunity, and the entrepreneurial environment affect the demand and supply of VC. The quantitative results, based on a panel dataset of 16 OECD countries from 1990 to 2000, show that VC intensity is pro-cyclical. Interest rates affect more the demand side of VC (entrepreneurs) than the supply side. Indicators of technological opportunity, such as the stock of knowledge and the number of triadic patents affect positively and significantly the relative level of VC. Labour market rigidities reduce the impact of the GDP growth rate and of the stock of knowledge, whereas a minimum level of entrepreneurship is required in order to have a positive effect of the available stock of knowledge on VC intensity.
Keywords: O33; G24; M13; C33; 330; Venture Capital; Technological Opportuniy; Entrepreneurship; Labour Market Regidities; Risikokapital; Innovationsdiffusion; Unternehmer; Arbeitsmarktflexibilisierung; Schätzung; OECD-Staaten